h.hofstede (h.hofstede@hogeland.nl)

1. 4 + 5(5a 3)
= 4 + 25a - 15
= 25a  - 11
   
       
2. -6(3q 2p)
= -6 3q - 6 -2p
= -18q + 12p
   
       
3. 3p(2 + 6p)
= 3p 2 + 3p 6p
= 6p + 18p2
   
       
4. 3(4p + 2q) 4(4q 5p)
= 12p + 6q - 16q + 20p
=
32p - 10q
   
       
5. 6 (y - 5)
= 6 -1 y - 1 -5
= 6 - y + 5
= 11 - y
   
       
6. 10 2(- 4a 3b)
= 10 - 2 -4a  - 2 -3b
= 10 + 8a + 6b
   
       
7. 2x - x(4 - 3x) + 2x2
= 2x - 4x + 3x2  + 2x2
= -2x + 5x2
   
       
8. 3x - 7(3 + x)
= 3x - 21 - 7x
= -4x - 21
   
       
9. -a(-2 4b) + 3a(5 6a)
= 2a + 4ab + 15a - 18a2
= 17a + 4ab - 18a2
   
       
10. 4a 2a (-4 + b)
= 4a + 8a - 2ab
= 12a - 2ab
   
       
11. 4a(2a - 3) - a(6 - 5a)
= 8a2 - 12a - 6a + 5a2
= 13a2 - 18a
   
       
12. 14x 3x(6 y)
= 14x - 18x + 3xy
= -4x + 3xy
   
       
13. -2(5x 6y)
= -2 5x  - 2 -6y
= -10x + 12y
   
       
14. -2p(4 - p) + 3p(2p + 7)
= -8p + 2p2 + 6p2 + 21p
= 13p + 8p2 
   
       
15. -4(x + 2y) 3x(5 2y)
= -4x - 8y - 15x + 6xy
= -19x - 8y + 6xy
   
       
16. 2a(b + 4) - 3b(6 - a)
= 2ab + 8a - 18b + 3ab
= 5ab + 8a - 18b
   
       
17. 6p - 2(3p - 5) - 5p
=
6p - 6p + 10 - 5p
= 10 - 5p
   
       
18. 8x - (4 - 3x)
= 8x - 4 + 3x
= 11x - 4
   
       
19. 2 - (4x - 5) + 3(-2x + 2)
= 2 - 4x + 5 - 6x + 6
= 13 - 10x
   
       
20. 6m(2n + 8) - 3n(12 - m)
= 12mn + 48m - 36n + 3mn
=
15mn + 48m - 36n
   
       

h.hofstede (h.hofstede@hogeland.nl)